Bilateral anomalous origin of the medial circumflex femoral artery : a case report - Mahesh Sharma, Megha Rapotra, Amandeep Kaur, Anshu Sharma, (International Journal of Scientific Research and Management (IJSRM), 2015)
Aim :The femoral artery (FA) and its branches play important roles in the arterial supply of the lower extremity. If the femoral artery is occluded, the circulation of the extremity is maintained by certain anastomoses. Therefore, identification of variations of these arteries is critical from a clinical and surgical point of view. Method : Present study was done during routine dissections at the Department of Anatomy, Government Medical College and Hospital, Chandigarh, India. Observations: A bilateral variation of the medial circumflex femoral artery (MCFA) was observed in a formalin-fixed cadaver. In this case, on the right side MCFA branched off from the posterolateral aspect of the FA and on the left side artery arose from the common trunk of femoral artery with the deep femoral artery. Conclusion : The morphological knowledge will helps the surgeons to avoid complications like catastrophic bleeding and diagnostic misinterpretations